A laboratory investigation of inbank flow characteristics in a straight compound channel [electronic resource] - Mohd Amirul Ashraf Ibrahim, 1988-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2011